A systematic review of adverse events of rifapentine and isoniazid compared to other treatments for latent tuberculosis infection. Issue 6 (23rd March 2018) - Pease, Christopher; Hutton, Brian; Yazdi, Fatemeh; Wolfe, Dianna; Hamel, Candyce; Barbeau, Pauline; Skidmore, Becky; Alvarez, Gonzalo G.
Abstract: Purpose: Tuberculosis (TB) remains a common cause of death globally. A regimen of 12 doses of isoniazid (INH) and rifapentine given once weekly (INH/RPT‐3) has recently been recommended by the World Health Organization for the treatment of latent TB infection (LTBI). We aimed to determine whether the INH/RPT‐3 regimen had similar or lesser rates of adverse events compared to other LTBI regimens, namely INH for 9 months, INH for 6 months, rifampin for 3 to 4 months, and rifampin plus INH for 3 to 4 months. Methods: We searched MEDLINE, Embase, CENTRAL, PubMed, ICTRP, clinicaltrials.gov, and Canadian Agency for Drugs and Technologies in Health's Gray Matters Light for randomized, postmarketing, and comparative nonrandomized studies of patients with confirmed LTBI that reported the frequency of at least 1 adverse event of relevance for a regimen of interest. The search included studies published until March 2017. The frequencies of adverse events were extracted and are presented descriptively. Results: Data from 23 randomized and 55 nonrandomized studies were included. Although inconsistent event reporting and high heterogeneity limited comparisons, the adverse event profile of INH/RPT‐3 appeared generally favorable. Flu‐like reactions were reported with an increased frequency and hepatotoxicity with a lower frequency than standard treatment. Conclusions: While INH/RPT‐3 had an overall low frequency of adverse events compared to INH monotherapy, reporting of adverse events for many regimens was limited meaning results should be interpreted cautiously. Future studies of LTBI treatment would benefit from more complete collection and reporting of adverse events and more consistent definitions of hepatotoxicity.